Pancasila sebagai dasar ideologi bangsa indonesia: analisis filosofis perbandingan pancasila dengan ideologi-ideologi dunia - Rahmawati, Sherly (Maliki Interdisciplinary Journal, 2025)
The basis of the state and ideology of the Indonesian nation is Pancasila, which has a very important role in determining the direction of the goals and formation of the state. This article discusses the understanding of Pancasila, the essence of the Pancasila principles, and its position as an ideology for the Indonesian nation that explains universal values. Pancasila as an ideology has dynamic and inclusive characteristics that allow it to adapt to the development of the times without losing its essence, and is able to accommodate the diversity of cultures and values that exist in Indonesia. This article also discusses the comparison of Pancasila with several other ideologies, such as liberalism, socialism, fascism, and conservatism, to show how Pancasila integrates the best elements of various world thought systems. Thus, the function of Pancasila is not only as the basis of the state, Pancasila is also an ideology that is relevant in facing political, economic, and social challenges at various levels.